Pengaruh Ikatan Relasional dan Kepercayaan terhadap Niat Beli Ulang pada Shopee Live (Effect of Relational Bonds and Trust on Repurchase Intention in Shopee Live) - Rafiqatul hikmah (Akutansi Bisnis & Manajemen ( ABM ), 2026)
This study aims to analyze the influence of relational bonds—including financial, social, and structural bonds—as well as consumer trust on repurchase intention among Shopee livestreaming users. A quantitative approach was employed using a survey method involving 200 respondents. The data were analyzed using PLS-SEM. The results indicate that structural bonds have a significant effect on trust in the host, while financial and social bonds do not show a significant effect. Trust in the host significantly influences trust in the product but does not directly impact repurchase intention. These findings suggest that consumer trust—particularly trust in the product—is a key factor in driving repurchase behavior, influenced by structural aspects and trust in the host.